The Existence of Tri Datu, From Temple's gift to Souvenir Industry - Eka Ari Suhendra (Bali Tourism Journal, 2021)
Consisting of three colors: red, white, and black, Tri Datu reflects three absolute powers surrounding the universe. Balinese Hindu people manifest the trinity deities into interwoven red, black and white threads. Almost in every Balinese Hindu ritual, the existence of the Tri Datu thread can be seen. Therefore, the Tri Datu thread has been using as a ritual instrument or protective amulet. On a philosophical level, the item has a value of self-control. If someone is wearing the sacred item, they would properly behave in society because the interwoven thread represents the divine symbol of righteousness. Many Balinese have been spotted wearing the three-colored thread, thus attracted the non-Balinese people curiosity. The phenomenon was perceived by wider communities that the interwoven thread is local identity. It is gradually led to market demand to obtain the Tri Datu as a souvenir from the island of God. One to another home industry of the Tri Datu accessories emerged as a response to tourism industry demand. Today, one may find the Tri Datu thread-based souvenir in the marketplace at ease. Although the interwoven thread strongly relates to religious symbols, it does not mean that non-Balinese cannot wear it. One should be aware that the Tri Datu holds a religious value that should be taken into account. Therefore, one should avoid wearing it inappropriately, such as a leg bracelet, or put it in any place without consulting it beforehand.